An ASP approach for reasoning in a concept-aware multipreferential lightweight DL. Issue 5 (September 2020) - Giordano, Laura; Theseider Dupré, Daniele
Abstract: In this paper we develop a concept aware multi-preferential semantics for dealing with typicality in description logics, where preferences are associated with concepts, starting from a collection of ranked TBoxes containing defeasible concept inclusions. Preferences are combined to define a preferential interpretation in which defeasible inclusions can be evaluated. The construction of the concept-aware multipreference semantics is related to Brewka's framework for qualitative preferences. We exploit Answer Set Programming (in particular, asprin ) to achieve defeasible reasoning under the multipreference approach for the lightweight description logic ξ $\mathcal L_ \bot ^ + $ .